Validity and reliability evidences of the Hit & Turn Tennis Test - Urso, R. P.; Okuno, N. M.; Gomes, R. V.; Lima-Silva, A. E.; Bertuzzi, R. (Science & Sports, 2014)
Objective: To investigate the validity and reliability of the Hit & Turn Tennis Test (HTTT). Equipment and methods: Ten recreational (RG) and ten trained (TG) tennis players performed the HTTT and the 20-m Multistage Shuttle Run Test (MSRT) on separate days and in a counterbalanced order. Additionally, ten recreational tennis players performed the retest of the HTTT. For both tests, the maximal distance covered (Dmax), time to exhaustion (TE), peak velocity achieved (Vpeak), estimated maximal oxygen uptake (VO2max-est), peak heart rate (HRpeak), blood lactate concentration before warm-up ([La]rest), and peak blood lactate concentration ([La]peak) were measured. Blood lactate concentration at the end of the fourth ([La]4o) and eighth ([La]8o) stages were measured in the HTTT. Results: Dmax, TE, Vpeak and VO2max-est were significantly higher for the TG compared to the RG (P < 0.01). [La]4o and [La]8o were significantly lower in the TG when compared to the RG (P < 0.01). There was no significant difference in Dmax, VO2max-est, HRpeak, [La]rest or [La]peak between the HTTT and MSRT for both groups (P > 0.05). Dmax, TE, VO2max-est, HRpeak, Vpeak, [La]4o and [La]8o were significantly reliable for the HTTT (the ICC ranged from 0.86 to 0.98, P < 0.01). A Bland-Altman analysis was also used and indicated high reliability in the HTTT for VO2max-est (1 ± 3.3 mL kg-1 min-1), Vpeak (0.12 ± 0.33 km h-1), [La]4o (0.39 ± 1.34 mmol L-1) and [La]8o (0.2 ± 2.7 mmol L-1).